Conceptualizing the Interaction of Buddhism and Daoism in the Tang Dynasty: Inner Cultivation and Outer Authority in the Daode Jing Commentaries of Cheng Xuanying and Li Rong - Assandri, Friederike (Religions, 2019)
This paper takes the different interpretations of one and the same sentences in the Daode jing as “inner cultivation” or “worldly power” respectively, in the commentaries of two closely related early Tang Daoist authors, Cheng Xuanying 成玄英 and Li Rong 李荣, as a starting point to approach the question of interaction of Buddhism and Daoism from a new angle. Instead of trying to pinpoint influences, origins, and derivatives, I propose to delineate philosophical discourses that cross the boundaries of the three teachings. Parallel excerpts from both commentaries show how Cheng reads the Daode jing as a guidebook for cultivation, and how Li Rong reads it as a guideline for governing. I argue that the differences could be read as the authors’ participation in different philosophical discourses, and I will show, for the case of Cheng Xuanying, how terminological overlap with contemporary Buddhist authors indicates that Buddhists and Daoists both participated in the discourse on inner cultivation with commentaries to their respective sacred scriptures.